Evaluation Pension System as a Primary Source of Social Security in Uzbekistan - Kuziyeva Gulnoza Rashidovna (European Science Publishing, 2023)
Uzbekistan has implemented a range of social protection programs; however, a significant limitation lies in the inadequate consolidation of data, hindering comprehensive monitoring and evaluation of program effectiveness. It is essential to establish a robust monitoring and evaluation framework and enhance statistical capacity to facilitate coherent analysis of social protection initiatives and the overall system. This will enable policymakers to make informed decisions regarding policies and budget allocations. While the financing and coverage of social assistance programs have expanded in response to the pandemic, it is anticipated that these figures will revert to pre-COVID-19 levels. This outcome is influenced by the current budgeting approach for social assistance, which relies on historical trends and regional quotas rather than needs-based determinants.